Description of Anxiety Regarding the Smoothness of Breast Milk in Breastfeeding Mothers in the West Lombok Working Area - nisa, Annisa nisa (Jurnal Embrio, 2024)
Breast milk is the best source of nutrition for infants containing immune-boosting substances and providing natural protection. Anxiety experienced by mothers after childbirth can hinder breast milk production. The smoothness of breast milk production is influenced by psychological factors in mothers; when a mother experiences depression or anxiety, it can affect the smoothness of breast milk production. An anxious mother produces less breast milk than a non-anxious mother. Objective: To determine the Influence of Anxiety on the Smoothness of Breast Milk Production in Postpartum Mothers in the work area of ??UPT BLUD health center in Gunung Sari. Method: This research design used a cross-sectional approach with observational analytical methods. The sample of this study was postpartum mothers in the UPT health center Gunung Sari work area, totaling 38 people. Results: The frequency of respondents based on the level of anxiety was as follows: no anxiety category had 30 respondents (79%), mild anxiety had 8 respondents (21%). The frequency of breast milk production was as follows: 32 respondents (84%) had smooth breast milk production, 6 respondents (16%) had non-smooth breast milk production. Bivariate analysis using the chi-square test obtained a p-value of 0.026, which is smaller than the significance value of 0.05. Conclusion: There is an influence of anxiety on the smoothness of breast milk production in postpartum mothers in the work area of ??UPT BLUD health center Gunung Sari. Recommendations: Health workers, especially those in UPT BLUD health center Gunung Sari, are advised to recommend to postpartum mothers to maintain the quality of their breast milk.